First extra-Patagonian record of Podocarpaceae fossil wood in the Upper Cenozoic (Ituzaingó Formation) of Argentina - Franco, María Jimena (2015)
The main objective of the present paper is to describe a new genus and species of Podocarpaceae fossil wood from the Upper Cenozoic Ituzaingó Formation, Paraná Basin, Argentina, based on a detailed description of the secondary xylem. This specimen, Prumnopityoxylon gnaedingerae Franco & Brea gen. nov. & sp. nov., is the first fossil wood referable as coniferous from northeastern Argentina. This fossil resembles extant Prumnopitys Phil. (Podocarpaceae), sharing the following anatomical features: slightly distinct growth rings; the absence of axial parenchyma; uniseriate and homocellular rays; uniseriate or biseriate, opposite or sub-opposite, separate or contiguous tracheid pitting; and cupressoid or taxodioid cross-field pitting. The presence of this Podocarpaceae fossil from the Ituzaingó Formation indicates that the distribution of this family was more widespread and probably continuous in South America in the past. It also provides new evidence for the hypothesis of its wide distribution in northeastern Argentina during the Cenozoic.